2023
DOI: 10.1289/ehp10653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Neighborhood-Level Differences in Hair Product Safety by Environmental Working Group Ratings among Retailers in Boston, Massachusetts

Marissa Chan,
Shivani Parikh,
Derek Shyr
et al.

Abstract: Background: Personal care products are a notable source of exposure to endocrine-disrupting chemicals (EDCs). Racial/ethnic differences in the use of hair products containing EDCs are reported, with women and children of color more commonly using hair products that are hormonally active and contain EDCs than other racial/ethnic groups. There is limited research examining the neighborhood-level social and economic factors that may contribute to these reported disparities. Objectives:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Given the lack of data on the product brands, we were not able to provide empirical evidence to evaluate this hypothesis in the current analysis. However, many beauty products that advertise the omission of nonpersistent EDCs from their ingredient list (e.g., phthalates and parabens) tend to be more expensive and less accessible to individuals of lower SES. ,− For example, a 2023 study found that stores in lower income communities and communities of color had a higher prevalence of toxic hair products (as classified by the Environmental Working Group’s hazard score) . Future studies should investigate the types and brands of personal care products marketed and used across SES groups among Black women and the levels of nonpersistent EDCs within those products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the lack of data on the product brands, we were not able to provide empirical evidence to evaluate this hypothesis in the current analysis. However, many beauty products that advertise the omission of nonpersistent EDCs from their ingredient list (e.g., phthalates and parabens) tend to be more expensive and less accessible to individuals of lower SES. ,− For example, a 2023 study found that stores in lower income communities and communities of color had a higher prevalence of toxic hair products (as classified by the Environmental Working Group’s hazard score) . Future studies should investigate the types and brands of personal care products marketed and used across SES groups among Black women and the levels of nonpersistent EDCs within those products.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we have previously found that personal care product use (e.g., self-reported use of hair products) differed by SES among participants in the SELF cohort, which has important implications for potential EDC exposure. A 2023 study in Boston further reported that lower income communities and communities of color had a greater number of high hazard personal care products in retail stores comparatively to higher SES and non-Hispanic White communities, suggesting that access to less toxic products may affect EDC exposures across SES groups.…”
Section: Introductionmentioning
confidence: 99%